Infections in gynecology and obstetrics. Sepsis and septic shock in obstetrics and gynecology. - Gonzáles Enders, Rodolfo (2015)
There are many definitions of shock, but the simplest and operational is one that defines it as a state of poor vascular perfusion, especially at the peripheral level. In arterial, arteriovenous and venous vessels of a haven blood circulation, leading to tissue anoxia develops, which in turn initiates the metabolic acidotic and coagulation disorders, which ultimately deepen the process and that, not eliminated because they can cause the death of the host.